Strategi KUA dalam Sosialisasi Dampak Negatif Pernikahan Usia Dini bagi Remaja di Desa Simpang Marbau - Raihan Budi Adriansyah; Khatibah Khatibah (Universitas Cokroaminoto Yogyakarta, 2026)
This study aims to determine the strategy of the KUA in socializing the negative impacts of early marriage for teenagers in Simpang Marbau Village, Na lX-X District, North Labuhanbatu Regency. Law No. 16 of 2019 concerning has set the minimum age of marriage to 19 years for men and women. The method used is qualitative with descriptive analysis. The data collection technique used is interview observation. The results obtained in this study are that the KUA strategy is guidance for school-aged teenagers, socialization during premarital guidance, community-based education socialization through social campaign media and digital literacy, local transformation applied in socializing the negative impacts of early marriage.